Aplicable law to international donations - Goñi Urriza, Natividad (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
The article deals with the determination of the applicable law to donations in Spanish Private International Law. The coexistence of conflict of law rules included in Rome I and successions European Regulations makes necessary to distinguish between different types of donations. Additionally, the article addresses the unavoidable application of the rules of national private international law for the determination of the law applicable to some aspects of the rights in rem.